Severe Hypothyroidism due to the Loss of Therapeutic Efficacy of l-Thyroxine in a Patient with Esophageal Complication Associated with Systemic Sclerosis - Lobasso, Antonio; Nappi, Liliana; Barbieri, Letizia; Peirce, Carmela; Ippolito, Serena; Arpaia, Debora; Rossi, Francesca Wanda; de Paulis, Amato; Biondi, Bernadette (Frontiers in Endocrinology, 2017)
ABSTRACT Background: Thyroid function abnormalities and thyroid autoantibodies have been frequently described in patients with systemic autoimmune diseases as Systemic Sclerosis (SSc). Serum TSH levels are higher in SSc patients with more severe skin diseases and a worse modified Rodnan skin score (mRSS). Asymptomatic esophageal involvement due to SSc has never been described as a cause of severe hypothyroidism due to L-T4 malabsorption in patients with HT and SSc. Case report: Here we report a case of a 56-year-old female affected by both SSc and Hashimoto's thyroiditis (HT) who developed severe hypothyroidism due to the loss of therapeutic efficacy of L-thyroxine (L-T4). Therapeutic failure resulted from the altered L-T4 absorption because of SSc esophageal complications. Clinical findings improved after the administration of oral liquid L-T4. Thyroid function completely normalized with a full clinical recovery, the disappearance of the pericardial effusion and the improvement of the pulmonary pressure. Conclusion: A recognition of a poor absorption is crucial in patients with hypothyroidism and SSc to reduce the risk of the subsequent adverse events. This case suggests the importance of clinical and laboratory surveillance in patients with SSc and HT because the systemic complications of these dysfunctions may worsen the prognosis of hypothyroid SSc/HT patients.